2007
DOI: 10.1128/mcb.00384-07
|View full text |Cite|
|
Sign up to set email alerts
|

Aquaporin 7 Is a β-Cell Protein and Regulator of Intraislet Glycerol Content and Glycerol Kinase Activity, β-Cell Mass, and Insulin Production and Secretion

Abstract: To investigate if intracellular glycerol content plays a role in the regulation of insulin secretion in pancreatic ␤ cells, we studied the expression of the glycerol channels, or aquaglyceroporins, encoded by the aquaporin 3 (Aqp3), Aqp7, and Aqp9 genes in mouse islets. We found expression of Aqp7 only, not that of Aqp3 or Aqp9, in the endocrine pancreas at both the mRNA (by reverse transcription-PCR) and protein (by immunohistochemistry) levels. Immunohistochemistry revealed a complete overlap between insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 46 publications
0
57
0
Order By: Relevance
“…In both these lines, no effect on body weight or fat pad masses were detected, and neither were there any differences between KO and WT animals in the plasma levels of glycerol, FFA, or TGs (Matsumura et al 2007. Possible reasons for these variations could be due to different gene targeting strategies, different genetic backgrounds, or differences in collection and analysis of tissue samples.…”
Section: Effects Of Aqp7 Deficiency On Glycerol Metabolismmentioning
confidence: 91%
See 2 more Smart Citations
“…In both these lines, no effect on body weight or fat pad masses were detected, and neither were there any differences between KO and WT animals in the plasma levels of glycerol, FFA, or TGs (Matsumura et al 2007. Possible reasons for these variations could be due to different gene targeting strategies, different genetic backgrounds, or differences in collection and analysis of tissue samples.…”
Section: Effects Of Aqp7 Deficiency On Glycerol Metabolismmentioning
confidence: 91%
“…Despite the apparent intracellular localization of AQP7, the AQP7 KO mice were reported to have a higher intra-islet glycerol and TG content with an increased activity of GlyK similar to that observed in WAT from the first KO line. This was accompanied by an increased secretion of insulin, increased p-insulin levels with no effect on p-glucose, and with no evidence of insulin resistance (Matsumura et al 2007). Owing to the wide expression profile of AQP7, the relative contribution of the different tissues to the phenotype of the total AQP7 KO mouse model seems difficult to define.…”
Section: Effects Of Aqp7 Deficiency On Glycerol Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Hibuse et al [11] demonstrated that Aqp 7-knockout mice developed insulin resistance after consumption of a high-fat/high-sucrose diet. Moreover, Aqp 7-knockout mice show hyperinsulinemia and increased pancreatic insulin-1 and insulin-2 transcript levels [26]. However, AQP7 does not correlate with either serum insulin levels or the HOMA IR from subcutaneous or visceral adipose tissue obtained from severely obese or type 2 diabetic humans [27].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the reduction in b-cell mass observed in Aqp7 ¡/¡ mice can be explained at least in part by a reduction in cell proliferation through protein kinase C and the cmyc cascade, with a reduction in the transcript levels of the esponding two genes. 68 AQP9 is the primary route of hepatocyte glycerol uptake for gluconeogenesis. 69 In mouse memory T cells, it can act as a metabolic switch, enabling longterm survival of the cells by enabling triglyceride synthesis to build up an energetic reserve, allowing survival under nutrient-poor conditions.…”
Section: Glycerolmentioning
confidence: 99%